Long-Term Sex-Dependent Vulnerability to Metabolic challenges in Prenatally Stressed Rats - Panetta, Pamela; Berry, Alessandra; Bellisario, Veronica; Capoccia, Sara; Raggi, Carla; Luoni, Alessia; Longo, Linda; Riva, Marco A.; Cirulli, Francesca (Frontiers in Behavioral Neuroscience, 2017)
Prenatal stress (PNS) might affect the developmental programming of adult chronic diseases such as metabolic and mood disorders. The molecular mechanisms underlying such regulations may rely upon long-term changes in stress-responsive effectors such as Brain-Derived Neurotrophic Factor (BDNF) that can affect neuronal plasticity underlying mood disorders and may also play a role in metabolic regulations. Based upon previous data, we hypothesized that PNS might lead to greater vulnerability to an obesogenic challenge experienced at adulthood. In order to investigate our hypothesis, pregnant Sprague-Dawley female rats underwent a chronic procedure of restraint stress during the last week of gestation. The adult offspring were then challenged with a high fat diet (HFD) over 8 weeks and tested for metabolic and emotional endpoints. Moreover, brain specific changes in Bdnf expression levels were also assessed. Overall, HFD resulted in increased caloric intake, insulin resistance, impaired glucose tolerance and higher circulating levels of leptin, while PNS increased the leptin/adiponectin ratio, an index of metabolic risk in adult male subjects. Interestingly, HFD consumption increased anxiety-like behaviors in the Elevated Plus Maze, particularly in males, and this effect was buffered by PNS. Levels of Bdnf were finely modulated by PNS and HFD in a region- and sex-dependent fashion: female offspring overall showed greater plasticity, possibly mediated through increased total Bdnf mRNA expression both in the hippocampus and in the hypothalamus. In conclusion, while the experience of maternal stress during intrauterine life promotes metabolic dysfunction induced by a HFD at adulthood, the interaction between PNS and HFD is positive in male subjects, and in agreement with the match-mismatch hypothesis, resulting in a reduction of anxious behaviors.